Sosialisasi Membangun Budaya Literasi Dengan Jurnal Membaca Harian - Fatimah Zahara, Siti; Deliany, Susi; Muliatik, Sri; Arianto, Arianto; Harahap, Andi Syahputra (Jurnal Pengabdian Masyarakat Inovasi, 2024)
The low level of literacy culture among students is a serious challenge in Indonesian education that requires practical and sustainable solutions. This community service activity aims to build a literacy culture among 8th-grade students at SMP Negeri 1 Deli Tua through the socialization and implementation of daily reading journals. The implementation method used was classical guidance services, including material presentation, participatory group discussions, digital literacy practices, and the formulation of personal action plans. The daily reading journal was utilized as the primary instrument to monitor students' reading activities in a measurable and disciplined manner. The results of the activity showed a significant positive impact on students' reading interest and analytical skills. Students demonstrated high enthusiasm in selecting reading materials and were able to consistently submit reading summaries. The daily journal successfully became a reflective medium that not only sharpened writing skills but also enhanced a deep understanding of the texts read. Furthermore, this activity strengthened the synergy between teachers and students in creating a school literacy ecosystem. The conclusion of this community service emphasizes that the use of daily reading journals, collaborated with dedicated reading hours, is an effective strategy for forming disciplined literacy habituation. It is recommended that schools integrate these journals into permanent academic policies to ensure the future sustainability of literacy culture.